2019
DOI: 10.4111/icu.2019.60.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior and sexually transmitted infection in the elderly population of South Korea

Abstract: Purpose To study the sexual behavior and status of sexually transmitted urethritis (STU) in the elderly population of South Korea. Materials and Methods Congregating places for elderly population, which were selected on the expected risk of sexually transmitted infections, were visited to study their sexual behavior, awareness on sexually transmitted diseases (STDs), and STU status using a specially developed survey and urine polymerase chain reaction (PCR) test. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
2
11
0
10
Order By: Relevance
“…A study in South Korea showed that sexually active elderly people, mainly men, had multiple sexual partners and a very low rate of condom use. Furthermore, the elderly who had a high knowledge of STI prevention and transmission had lower risk behaviour [ 38 ]. In the US, between 2008 and 2016, 757 people aged 65 years and above were diagnosed with HIV, and 92.6% of them reported having not used a condom.…”
Section: Discussionmentioning
confidence: 99%
“…A study in South Korea showed that sexually active elderly people, mainly men, had multiple sexual partners and a very low rate of condom use. Furthermore, the elderly who had a high knowledge of STI prevention and transmission had lower risk behaviour [ 38 ]. In the US, between 2008 and 2016, 757 people aged 65 years and above were diagnosed with HIV, and 92.6% of them reported having not used a condom.…”
Section: Discussionmentioning
confidence: 99%
“…More dangerous yet is the fact that elders succumb faster than younger persons to AIDS and, consequently, to death. [27][28][29][30] We did not nd any public health policy articulated to this demographic regarding STI prevention.…”
Section: Discussionmentioning
confidence: 95%
“…Estudo realizado na Coreia do Sul com pessoas acima de 65 anos mostrou que aquelas sexualmente ativas, principalmente os homens, mantinham múltipla parceria sexual e não costumavam usar o preservativo. Porém, os que detinham conhecimento sobre os riscos de infecções sexualmente transmissíveis (IST) praticavam sexo mais seguro 6 .…”
Section: Discussionunclassified
“…Nos Estados Unidos, em 2018, a cada seis diagnósticos de HIV, um deles era em pessoa acima de 50 anos de idade 5 . No Brasil, do total de novos casos notificados de HIV/Aids em 2008, a faixa etária de 50 anos representava 9,34%, passando para 12,42% em 2018 6 .…”
Section: Introductionunclassified